THEMATIC GROUPS OF OBSOLETE LEXICON IN PLAY "GROZE" OF A. N. OSTROVSKY - Kadhem, Munther Mulla; Hameed, Akram A. (Al-Adab Journal, 2020)
The article presents the thematic groups of outdated lexicon in the play “The Storm” written by A. N. Ostrovsky. The definitions of historicism and archaism have been identified in modern linguistics. It has been found out that in the play “The Storm” written by A. N. Ostrovsky the following groups of historicisms, including: historicism, naming the person (social position, personal dependence, titles); historicism, used to name the administrative-territorial units, land holdings, regions, associations, plots, houses, awards; historicism, which are used in the trade and economic sphere (means of payment, securities, money); historicism used to indicate measures, weight, length, liquids; and archaisms, including: 1) self-lexical; 2) lexico-semantic; 3) lexico-phonetic; 4) lexico-word formation archaisms have been determined.